1997
DOI: 10.1038/sj.leu.2400748
|View full text |Cite
|
Sign up to set email alerts
|

BCR/ABL-negative progenitors are enriched in the adherent fraction of CD34+ cells circulating in the blood of chronic phase chronic myeloid leukemia patients

Abstract: Philadelphia chromosome-positive (Ph + ) hemopoietic cells precan be mobilized, presumably from the bone marrow, into the dominate in patients with chronic myeloid leukemia (CML) in blood of CML patients following chemotherapy. 9 The blood of chronic phase, but some Ph − presumably normal stem cells CML patients has also been used for autologous rescue followpersist in most patients. Ph − cells are relatively frequent, coming high-dose therapy and in some cases Ph chromosomepared to mature cell populations, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

1998
1998
2003
2003

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 10 publications
2
12
0
Order By: Relevance
“…For patients with newly diagnosed BCR/ABL-positive CML, we showed that CD34 + HPC isolated from PB or BM are predominantly BCR/ABL-positive, which is in accordance with results reported by others. 28 We conclude that in the CML cases, the significantly increased proliferation is caused by BCR/ABLpositive HPC. As an additional confounder, one might argue that BCR/ABL-negative PBPC could be enriched among CD34 + /CD38 low cells.…”
Section: Discussionmentioning
confidence: 98%
“…For patients with newly diagnosed BCR/ABL-positive CML, we showed that CD34 + HPC isolated from PB or BM are predominantly BCR/ABL-positive, which is in accordance with results reported by others. 28 We conclude that in the CML cases, the significantly increased proliferation is caused by BCR/ABLpositive HPC. As an additional confounder, one might argue that BCR/ABL-negative PBPC could be enriched among CD34 + /CD38 low cells.…”
Section: Discussionmentioning
confidence: 98%
“…Coverslips were then removed, and the slides were washed twice in 2 ϫ SSC, thrice in 50% formamide/2 ϫ SSC pH 7.0-7.2, once in PBS, stained with DAPI, and mounted using Vectashield (Vector Laboratories Inc., Burlingame, CA). BCR-ABL-positive cells were identified by the coincidence of the green and orange signals (20).…”
Section: Fluorescence In Situ Hybridizationmentioning
confidence: 99%
“…Primitive pre-CFU-GM progenitor cells were assayed as previously described (18,19). The assay detects the activity of CD34-positive cells that are predominantly CD33, CD38, and HLA-DR negative and are capable of producing erythroid BFU-E as well as CFU-GM (19,20). In brief, the mononuclear cell fraction was separated from the blood and bone marrow samples by using Lymphoprep (Nycomed, Oslo, Norway), washed three times, and resuspended in alpha medium (GIBCO, Paisley, UK) supplemented with 15% FCS.…”
Section: Cell Culturementioning
confidence: 99%
“…We found that the frequency of Ph-negative cells was significantly higher in this cell population (P = 0.001) than amongst less primitive CD34-positive non-adherent cells, but that the majority (Ͼ80%) of the cells were Ph-positive. 2 The detection of BCR-ABL-negative primitive cells in CML patients in whom 100% of the mature cells are BCR-ABL-positive implies that normal cell proliferation is inhibited by the leukaemia clone. The mechanism for this suppression is not clear but might relate to negative feedback from the greatly increased neutophil count.…”
Section: Normal Cells In CMLmentioning
confidence: 99%
“…1 Another challenge is to document the fate of the residual normal haemopoietic stem cell population since this is crucial for the success of any treatment strategies apart from allogeneic bone marrow transplantation. The coexistence of primitive Ph-negative cells with primitive Ph-positive cells 2,3 and the virtual absence of mature Ph-negative cells from the blood and bone marrow of patients with chronic phase CML suggests that the Ph-positive clone suppresses mature cell production by normal Ph-negative pluripotent stem cells. Presumably, however, suppression of normal haemopoiesis requires some expansion of the Ph-positive clone, and is not a feature of CML at its inception.…”
Section: Introductionmentioning
confidence: 99%